ADVOKASI KEBIJAKAN TERHADAP PENDIDIKAN POLITIK MASYARAKAT MELALUI PROGRAM PARTAI AMANAT NASIONAL DI KABUPATEN LANGKAT - Khairunnisa, Shalsha; Sinaga, Rudi Salam; Lubis, Khairunnisah (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
Community political education programs are carried out PAN through recess and masa bimbingan anggota "Policy Advocacy for Community Political Education Through Programs Partai Amanat Nasional Kabupaten Langkat aims to make it easier Partai Amanat Nasional in carrying out activities and listening to community inspiration Langkat the problem in research is how to program Partai Amanat Nasional Kabupaten Langkat in conducting policy advocacy for public political education, what are the determinants of policy success and program inhibiting factors Partai Amanat Nasional in policy advocacy for community political education. Public Education Advocacy Policy has received support from the Government for Political Parties. Policy Partai Amanat Nasional Success factors, commitment, awareness, inhibiting factors, implementation time, area size, funds or money, national political situation, human resources, relations between administrators